Novel catalytic and mechanistic studies on wastewater denitrification with hydrogen - Theologidis, Christodoulos; Olympiou, Georgios; Savva, Petros G.; Pantelidou, Nantia; Constantinou, Barbara K.; Chatziiona, Vasiliki; Valanidou, Lilian; Piskopianou, Charoula; Costa, Costas (My University, 2014)
The present work reports up-to-date information regarding the reaction mechanism of the catalytic hydrogenation of nitrates in water media. In the present mechanistic study, an attempt is made, for the first time, to elucidate the crucial role of several catalysts and reaction parameters in the mechanism of the NO3-/H2 reaction. Steady-state isotopic transient kinetic analysis (SSITKA) experiments coupled with ex situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were performed on supported Pd-Cu catalysts for the NO3-/H2 and NO3-/H2/O2 reactions. The latter experiments revealed that the formation and surface coverage of various adsorbed active intermediate N-species on the support or Pd/Cu metal surface is significantly favored in the presence of TiO2 in the support mixture and in the presence of oxygen in the reaction's gaseous feed stream. The differences in the reactivity of these adsorbed N-species, found in the present work, adequately explain the large effect of the chemical composition of the support and the gas feed composition on catalyst behaviour (activity and selectivity). The present study leads to solid mechanistic evidence concerning the presence of a hydrogen spillover process from the metal to the support. Moreover, this study shows that Cu clusters are active sites for the reduction of nitrates to nitrites.
Keywords: Active species; Catalytic denitrification; DRIFTS; Mechanistic studies; SSITKA